Co-expression gene modules involved in cisplatin-induced peripheral neuropathy according to sensitivity, status, and severity - Zhou, Rui Hao; Chen, Chan; Jin, Su Han; Li, Jun; Xu, Zi Hao; Ye, Ling; Zhou, Jianguo (Journal of the Peripheral Nervous System, 2020)
Chemotherapy-induced peripheral neuropathy (CIPN) is among the most disabling and frustrating problems for cancer survivors. The neurotoxicity caused by cisplatin varies greatly among patients, and few predictors of appearance, duration of symptoms, susceptibility, or severity are available. A deeper understanding of the mechanisms underlying individual differences in status, severity, or sensitivity in response to cisplatin treatment is therefore required. By analyzing the GSE64174 gene expression profile and constructing a weighted gene co-expression network analysis (WGCNA) network, we screened gene modules and hub genes related to CIPN status, severity and sensitivity. We first identified the transcriptome profile of mouse dorsal root ganglion (DRG) samples and transformed their genes to human DRG counterparts. We then constructed WGCNA gene modules via optimal soft-threshold power-identification and module-preservation analysis. Comprehensive analysis and identification of module hub genes were performed via functional-enrichment analysis and significant common hub genes were identified, including “Cytoscape_cytoHubba,” “Cytoscape_MCODE,” and “Metascape_MCODE.” Brown, green, and blue modules were selected to represent CIPN sensitivity, status, and severity, respectively, via trait-module correlational analysis. Additionally, functional enrichment analysis results indicated that these three modules were associated with some crucial biological functions, such as neutrophil migration, chemokine-mediated signaling pathway, and PI3K-Akt signaling pathway. We then identified seven common hub genes via three methods, including CXCL10, CCL21, CCR2, CXCR4, TLR4, NPY1R, and GALR2, related to CIPN status, severity and sensitivity. Our results provide possible targets and mechanism insights into the development and progress of CIPN, which can guide further transformation and pre-clinical research.
CRIS-Team Scopus Importer:2020-09-11
Keywords: chemotherapy-induced peripheral neuropathy; cisplatin; hub gene; neuropathic pain; weighted gene co-expression network analysis

Development of a flow cytometry-based whole-blood prognostic immune signature in metastatic cancer patients treated with immune checkpoint inhibitors - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Eckstein, Markus; Sun, R.; Ma, H.; Schubert, Philipp; Schweizer, C.; Fietkau, Rainer; Deutsch, E.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Development of an immunological prognostic Signature in metastatic Patients who were treated with Immune Checkpoint Inhibitors as part of the ST-ICI Study - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Sun, R.; Ma, H.; Fietkau, Rainer; Deutsch, E.; Hecht, Markus; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Dissecting Tumor Antigens and Immune Subtypes of Glioma to Develop mRNA Vaccine - Zhong, Hua; Liu, Shuai; Cao, Fang; Zhao, Yi; Zhou, Jianguo; Tang, Feng; Peng, Zhaohua; Li, Yangsheng; Xu, Shen; Wang, Chunlin; Yang, Guohua; Li, Zhi Qiang (Frontiers in Immunology, 2021)
Background: Nowadays, researchers are leveraging the mRNA-based vaccine technology used to develop personalized immunotherapy for cancer. However, its application against glioma is still in its infancy. In this study, the applicable candidates were excavated for mRNA vaccine treatment in the perspective of immune regulation, and suitable glioma recipients with corresponding immune subtypes were further investigated. Methods: The RNA-seq data and clinical information of 702 and 325 patients were recruited from TCGA and CGGA, separately. The genetic alteration profile was visualized and compared by cBioPortal. Then, we explored prognostic outcomes and immune correlations of the selected antigens to validate their clinical relevance. The prognostic index was measured via GEPIA2, and infiltration of antigen-presenting cells (APCs) was calculated and visualized by TIMER. Based on immune-related gene expression, immune subtypes of glioma were identified using consensus clustering analysis. Moreover, the immune landscape was visualized by graph learning-based dimensionality reduction analysis. Results: Four glioma antigens, namely ANXA5, FKBP10, MSN, and PYGL, associated with superior prognoses and infiltration of APCs were selected. Three immune subtypes IS1–IS3 were identified, which fundamentally differed in molecular, cellular, and clinical signatures. Patients in subtypes IS2 and IS3 carried immunologically cold phenotypes, whereas those in IS1 carried immunologically hot phenotype. Particularly, patients in subtypes IS3 and IS2 demonstrated better outcomes than that in IS1. Expression profiles of immune checkpoints and immunogenic cell death (ICD) modulators showed a difference among IS1–IS3 tumors. Ultimately, the immune landscape of glioma elucidated considerable heterogeneity not only between individual patients but also within the same immune subtype. Conclusions: ANXA5, FKBP10, MSN, and PYGL are identified as potential antigens for anti-glioma mRNA vaccine production, specifically for patients in immune subtypes 2 and 3. In summary, this study may shed new light on the promising approaches of immunotherapy, such as devising mRNA vaccination tailored to applicable glioma recipients.
CRIS-Team Scopus Importer:2021-09-24
Keywords: glioma; immune landscape; immune subtypes; mRNA vaccine; tumor antigens

Editorial: Recent advances in genetic and proteomic biomarkers involved in the early detection of solid tumors - Li, Jitian; Chen, Apeng; Zhang, Ruowen; Li, Changwei; Zhou, Jianguo; Fang, Bin; Jiang, Yinan (Frontiers in Genetics, 2023)
CRIS-Team Scopus Importer:2023-09-29
Keywords: biomarker; detection; prognosis; solid tumor; treatment

Editorial: Uncovering Drug Resistance During Cancer Therapy - Wang, Haitao; Wang, Rui Hong; Zhou, Jianguo; Hou, Weilong; Wong, Ada Hang Heng (Frontiers in Genetics, 2022)
CRIS-Team Scopus Importer:2022-08-12
Keywords: biomarkers; cancer; cancer therapy; drug resistance; next generation sequencing; oncology

Effectiveness of ablative Irradiation of all Metastases versus Irradiation of a singular Metastasis in Combination with Immunocheckpoint Inhibitors - clinical Evaluation of prospective STICI Study - Schubert, P.; Schweizer, C.; Roesch, Johannes; Haderlein, Marlen; Rutzner, Sandra; Semrau, Sabine; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Hecht, Markus (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Effects of serial radon spa therapy on pain and peripheral immune status in patients suffering from musculoskeletal disorders– results from a prospective, randomized, placebo-controlled trial - Donaubauer, Anna-Jasmina; Becker, Ina; Klein, Gerhart; Voll, Reinhard E.; Weikl, Lena; Klieser, Martin; Barzangi, Shakar; Zhou, Jianguo; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2024)
In this randomized, placebo-controlled cross-over trial we aimed to investigate if radon spa therapy exerts more pain relief than exposure to warm water alone. In addition, immunological parameters were assessed in both treatment groups. In the RAD-ON02 trial, 116 patients suffering from musculoskeletal disorders (MSDs) received either serial radon spa or solely warm water baths. Pain intensity was assessed by determination of different pain parameters on a visual analogue scale and by pressure point dolorimetry at baseline and at weeks 4, 12 and 24. The longitudinal immune status of the patients was analyzed by a flow cytometry-based assay from peripheral blood at the time points of pain assessments. There were no side effects attributable to radon exposure observed. However, radon spa was superior to warm water applications at week 4 in terms of pain reduction. Pain and morning stiffness at the time of assessment were significantly reduced after radon spa (p<0.001, p<0.01) but not after warm water baths. The dolorimetry resulted in a significantly higher exerted pressure strength in patients after radon spa (p<0.001), but not after warm water applications. During the long-term follow-up, both treatment modalities reduced pain to a similar degree and pain modulation was not distorted by the participants’ intake of analgesics. No significant changes in the immune status attributable specifically to radon were found, even though the increase in regulatory T cell counts occurs earlier after radon baths than after sole warm water baths and a higher level of significance is reached after radon spa at week 24. Serial radon spa has additive pain-relieving effects. The immunological parameters assessed in our study appear not to be directly linked to the pain reduction caused by radon exposure, at least in MSD patients with predominantly degenerative diseases. Clinical trial registration: https://www.clinicaltrialsregister.eu/ctr-search/search?query=rad-on02, identifier 2016-002085-31; https://drks.de/search/de/trial, identifier DRKS00016019.
CRIS-Team Scopus Importer:2024-03-01
Keywords: chronic degenerative and inflammatory diseases; chronic pain; musculoskeletal disorders; peripheral immune status; radon spa; randomized placebo-controlled trial

Identification of an endogenous retroviral signature to predict anti-PD1 response in advanced clear cell renal cell carcinoma: an integrated analysis of three clinical trials - Zhou, Jianguo; Zeng, Yu; Wang, Haitao; Jin, Su-Han; Wang, Yun-Jia; He, Sisi; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Ma, Hu; Zhang, Wenchuan; Gaipl, Udo (Therapeutic Advances in Medical Oncology, 2022)
Background: Endogenous retrovirus (ERV) elements are genomic footprints of ancestral retroviral infections within the human genome. Previous studies have demonstrated that dysregulated ERV transcription level is associated with immune cell infiltration in cancers, but the association between ERV expression and programmed cell death protein 1 (PD-1) blockade response is currently unraveled for solid cancers, such as advanced clear cell renal cell carcinoma (ccRCC). Methods: ERV mRNA profiles were obtained from three clinical trials of ccRCC where the patients were treated with anti-PD-1 (CM-009, CM-010, CM-025, and TCGA-KIRC data). Patients treated with nivolumab were divided into training and test cohort, while the TCGA-KIRC cohort was used as an external validation. Univariate Cox regression analysis and least absolute shrinkage and selection operator regression were used to establish the signature. Immune cell infiltration analysis and gene set enrichment analysis were performed to explore potential biological mechanisms. Results: An ERV signature was established based on nine ERV expression patterns. In the training cohort, the median overall survival in the low- and high-risk group was 45.2 and 19.6 months [hazard ratio (HR) = 0.49, 0.32-0.75, p < 0.001], respectively. The results were confirmed in the test (HR = 0.41, 0.20-0.83, p = 0.013), and in the TCGA-KIRC cohort (HR = 0.55, 0.34-0.90, p = 0.017). Moreover, in the CM-025 cohort, the low-risk group that received nivolumab had a more favorable survival compared with those that received the mTOR inhibitor everolimus, while no significant differences were observed in the high-risk group. CD8+ T cells were enriched in the low-risk group, while immune suppressive pathways were suppressed. Conclusion: The newly identified ERV signature is not only a prognostic, but also a predictive biomarker for advanced ccRCC patients who received anti-PD-1 therapy, which can guide personalized treatment in cancer patients in the future.
CRIS-Team WoS Importer:2022-10-14

Implementation of double immune checkpoint blockade increases response rate to induction chemotherapy in head and neck cancer - Semrau, Sabine; Gostian, Antoniu Oreste; Traxdorf, Maximilian; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Hautmann, Matthias; Klautke, Gunther; Laban, Simon; Brunner, Thomas; Tamaskovics, Bálint; et al. (Cancers, 2021)
To determine whether a single dose of double immune checkpoint blockade (induction chemoimmunotherapy (ICIT)) adds benefit to induction single-cycle platinum doublet (induction chemotherapy (IC)) in locally advanced head and neck squamous cell carcinoma (HNSCC), patients treated with cisplatin 30 mg/m2 d1-3 and docetaxel 75 mg/m2 d1 combined with durvalumab 1500 mg fixed dose d5 and tremelimumab 75 mg fixed dose d5 (ICIT) within the CheckRad-CD8 trial were compared with a retrospective cohort receiving the same chemotherapy (IC) without immunotherapy. The endpoint of this analysis was the complete response rate (CR). A total of 53 patients were treated with ICIT and 104 patients with IC only. CR rates were 60.3% for ICIT and 40.3% for IC (p = 0.018). In the total population (n = 157), the most important predictor to achieve a CR was treatment type (OR: 2.21 for ICIT vs. IC; p = 0.038, multivariate analysis). The most diverse effects in CR rates between ICIT and IC were observed in younger (age ≤ 60) patients with HPV-positive OPSCCs (82% vs. 33%, p = 0.176), while there was no difference in older patients without HPV-positive OPSCCs (53% vs. 48%). The analysis provides initial evidence that ICIT could result in higher CR rates than IC. Young patients with HPV-positive OPSCCs may have the greatest benefit from additional immune checkpoint inhibitors.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Combined modality therapy; Double immune checkpoint inhibition; Head and neck neoplasms; HPV-positive OPSCC; Immunotherapy; Induction therapy; Organ preservation

Induction chemoimmunotherapy followed by CD8+ immune cell-based patient selection for chemotherapy-free radioimmunotherapy in locally advanced head and neck cancer - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias Günther; Brunner, Thomas B.; Tamaskovics, Bálint; Hinke, Axel; Zhou, Jianguo; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Purpose The first aim of the trial is to study feasibility of combined programmed death protein ligand 1/cytotoxic T-lymphocyte-associated protein 4 inhibition concomitant to radiotherapy. In addition, efficacy of the entire treatment scheme consisting of induction chemoimmunotherapy followed by chemotherapy-free radioimmunotherapy (RIT) after intratumoral CD8 +immune cell-based patient selection will be analyzed. Methods Patients with stage III-IVB head and neck squamous cell carcinoma were eligible for this multicenter phase II trial. Treatment consisted of a single cycle of cisplatin 30 mg/m² days 1-3, docetaxel 75 mg/m² day 1, durvalumab 1500 mg fix dose day 5 and tremelimumab 75 mg fix dose day 5. Patients with increased intratumoral CD8 +immune cell density or pathological complete response (pCR) in the rebiopsy entered RIT up to a total dose of 70 Gy. Patients received further three cycles of durvalumab/tremelimumab followed by eight cycles of durvalumab mono (every 4 weeks). The intended treatment for patients not meeting these criteria was standard radiochemotherapy outside the trial. Primary endpoint was a feasibility rate of patients entering RIT to receive treatment until at least cycle 6 of immunotherapy of ≥80%. Results Between September 2018 and May 2020, 80 patients were enrolled (one excluded). Out of these, 23 patients had human papilloma virus (HPV)-positive oropharyngeal cancer. Median follow-up was 17.2 months. After induction chemoimmunotherapy 41 patients had pCR and 31 had increased intratumoral CD8 +immune cells. Of 60 patients entering RIT (primary endpoint cohort), 10 experienced imiting toxic (mainly hepatitis) and four discontinued for other reasons, resulting in a feasibility rate of 82%. The RIT cohort (n=60) had a progression-free survival (PFS) rate at one and 2 years of 78% and 72%, respectively, and an overall survival rate at one and 2 years of 90% and 84%, respectively. Patients with HPV-positive oropharyngeal cancers had greater benefit from RIT with a 2-year PFS rate of 94% compared with 64% for HPV-negative oropharyngeal cancers and other locations. In the entire study cohort (n=79) the 2-year PFS rate was 68% (91% for HPV-positive oropharynx vs 59% for others). Toxicity grade 3-4 mainly consisted of dysphagia (53%), leukopenia (52%) and infections (32%). Conclusions The trial met the primary endpoint feasibility of RIT. Induction chemo-immunotherapy followed by chemotherapy-free RIT after intratumoral CD8 +immune cell-based patient selection has promising PFS. Trial registration number The trial was registered with ClinicalTrials.gov (identifier: NCT03426657). The trial was conducted as investigator-sponsored trial (IST).
CRIS-Team Scopus Importer:2022-02-11
Keywords: radioimmunotherapy

Influence of marital status on overall survival in patients with ovarian serous carcinoma: Finding from the surveillance epidemiology and end results (SEER) database - Luo, Pei; Zhou, Jianguo; Jin, Su Han; Qing, Ming Song; Ma, Hu (Journal of Ovarian Research, 2019)
Objective: This study is to investigate the relationship between marital status and prognosis of patients with ovarian serous carcinoma. Results: We performed data analysis from 19,276 patients identified from the SEER database of the National Cancer Center of the United States. 57.8% of the patients were married, 13.0% unmarried, and 29.2% separated/ divorced/widowed (SDW). The median overall survival time ofthe unmarried group and the married group are 48 months and 52 months respectively. Univariate Cox regression analysis showed that the patients with serous ovarian cancer in the unmarried group resulted in a hazard ratio (HR) of 1.14 (95% CI: 1.08-1.19%; P < 0.001), comparing to SDW group with a HR of 1.02 (95% CI: 0.98-1.19%; P = 0.26). However, the SDW group was not statistically significantly different from the married group. (median 32 vs 52 months). Multivariate Cox regression analysis presented the unmarried group leading to a HR of 1.05 (95% CI: 1.00-1.11%; P = 0.05), and the SDW group was not significant with a HR of 0.99 (95% CI: 0.95-1.03%; P = 0.57). Conclusion: Unmarried patients with ovarian serous carcinoma have higherHRof overall survival. After controlling age, race, grade, radiation and year of diagnosis, unmarried patients were found to have a significantly higher risk of OS. Consequently, these patients are suggested to obtain more focused healthcare for the management of ovarian serous carcinoma.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Marital status; Ovarian serous carcinoma; Overall survival; SEER

Integrative evaluation of primary and metastatic lesion spectrum to guide anti-PD-L1 therapy of non-small cell lung cancer: results from two randomized studies - Ma, Si-Cong; Tang, Xin-Ran; Long, Li-Li; Bai, Xue; Zhou, Jianguo; Duan, Zhi-Jiao; Wang, Jian; Fu, Qiang John; Zhu, Hong-Bo; Guo, Xue-Jun; Zhang, Yan-Pei; Guo, Ze-Qin; et al. (OncoImmunology, 2021)
Objectives: Clinical benefits of immune-checkpoint blockade (ICB) versus standard chemotherapy have been established in unselected non-small cell lung cancer (NSCLC). However, the response to ICB therapy among patients is heterogeneous in clinical practice.
CRIS-Team WoS Importer:2021-05-14

Low dose radiation therapy, particularly with 0.5 gy, improves pain in degenerative joint disease of the fingers: Results of a retrospective analysis - Donaubauer, Anna-Jasmina; Zhou, Jianguo; Ott, Oliver J.; Putz, Florian; Fietkau, Rainer; Keilholz, Ludwig; Gaipl, Udo; Frey, Benjamin; Weissmann, Thomas (International Journal of Molecular Sciences, 2020)
Low-dose radiation therapy (LDRT) has been successfully established for decades as an alternative analgesic treatment option for patients suffering from chronic degenerative and inflammatory diseases. In this study, 483 patients were undergoing LDRT for degenerative joint disease of the fingers and thumb at the University Hospital Erlangen between 2004 and 2019. Radiotherapy was applied according to the German guidelines for LDRT. Several impact factors on therapeutic success, such as the age and gender, the number of affected fingers, the single and cumulative dose, as well as the number of series, were investigated. In summary, 70% of the patients showed an improvement of their pain following LDRT. No significant impact was found for the factors age, gender, the number of series or the cumulative dosage. Patients with an involvement of the thumb showed a significantly worse outcome compared to patients with an isolated affection of the fingers. In this cohort, patients receiving a single dose of 0.5 Gy reported a significantly better outcome than patients receiving 1.0 Gy, strongly suggesting a reduction in the total dose. In summary, LDRT is a good alternative treatment option for patients suffering from degenerative and inflammatory joint disease of the fingers.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Chronic degenerative and inflammatory diseases; Degenerative joint disease of the fingers; LDRT; Low-dose radiation therapy; Osteoarthritis; Subjective pain level

Low-Dose Radiotherapy is highly effective in the Treatment of painful Finger Polyarthrosis - Weissmann, Thomas; Gaipl, Udo; Putz, Florian; Hecht, Markus; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Fietkau, Rainer; Ott, Oliver; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low-dose Radiotherapy is highly effective in the Treatment of Patients with painful Ankle Arthrosis - Weissmann, Thomas; Putz, Florian; Hecht, Markus; Zhou, Jianguo; Donaubauer, Anna-Jasmina; Fietkau, Rainer; Gaipl, Udo; Ott, Oliver; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low-Dose Radiotherapy Leads to a Systemic Anti-Inflammatory Shift in the Pre-Clinical K/BxN Serum Transfer Model and Reduces Osteoarthritic Pain in Patients - Weissmann, Thomas; Rückert, Michael; Zhou, Jianguo; Seeling, Michaela; Lettmaier, Sebastian; Donaubauer, Anna-Jasmina; Nimmerjahn, Falk; Ott, Oliver; Hecht, Markus; Putz, Florian; Fietkau, Rainer; Frey, Benjamin; et al. (Frontiers in Immunology, 2022)
Osteoarthritis (OA) is the leading degenerative joint disease in the western world and leads, if left untreated, to a progressive deterioration of joint functionality, ultimately reducing quality of life. Recent data has shown, that especially OA of the ankle and foot are among the most frequently affected regions. Current research in OA points towards a complex involvement of various cell and tissue types, often accompanied by inflammation. Low-dose radiotherapy (LDRT) is widely used for the treatment of degenerative and inflammatory diseases. While the reported analgesic effects are well known, the underlying molecular mechanisms are only poorly understood. We therefore correlated a clinical approach, looking at pain reduction in 196 patients treated with LDRT with a pre-clinical approach, utilizing the K/BxN serum transfer mouse model using flow cytometry and multiplex ELISA for analysis. While an improvement of symptoms in the majority of patients was found, patients suffering from symptoms within the tarsi transversa show a significantly lower level of improvement. Further, a significant impact of therapy success was detected depending on whether only one or both feet were affected. Further, patients of younger age showed a significantly better outcome than older ones while needing fewer treatment series. When looking on a cellular level within the mouse model, a systemic alteration of immune cells namely a shift from CD8+ to CD4+ T cells and reduced numbers of DCs was observed. A general reduction of inflammatory cytokines was detected, with significant alterations in IL-4 and IL-17 levels, all of which could potentially be responsible for the highly effective clinical improvement in patients. Taken together our data indicate that LDRT can be regarded as a highly effective treatment option for patients suffering from OA of the foot and ankle, in terms of analgesic effects, especially in younger patients. Furthermore, the observed effects are mediated by an interplay of cellular and soluble immune factors, as observed in the K/BxN serum transfer model. With this interdisciplinary approach we aim to encourage the usage of LDRT as an additive treatment strategy not only as a last resort, but also earlier in the course of disease.
CRIS-Team Scopus Importer:2022-01-28
Keywords: foot; K/BxN serum transfer; low-dose radiotherapy; mouse model; osteoarthritis; pain; rheumatoid arthritis; X-rays

Machine Learning-assisted immunophenotyping of peripheral blood identifies innate immune cells as best predictor of response to induction chemo-immunotherapy in head and neck squamous cell carcinoma – knowledge obtained from the CheckRad-CD8 trial - Hecht, Markus; Frey, Benjamin; Gaipl, Udo; Tianyu, Xie; Eckstein, Markus; Donaubauer, Anna-Jasmina; Klautke, Gunther; Illmer, Thomas; Fleischmann, Maximilian; Laban, Simon; Hautmann, Matthias G.; Tamaskovics, Bálint; et al. (Neoplasia, 2024)
Purpose: Individual prediction of treatment response is crucial for personalized treatment in multimodal approaches against head-and-neck squamous cell carcinoma (HNSCC). So far, no reliable predictive parameters for treatment schemes containing immunotherapy have been identified. This study aims to predict treatment response to induction chemo-immunotherapy based on the peripheral blood immune status in patients with locally advanced HNSCC. Methods: The peripheral blood immune phenotype was assessed in whole blood samples in patients treated in the phase II CheckRad-CD8 trial as part of the pre-planned translational research program. Blood samples were analyzed by multicolor flow cytometry before (T1) and after (T2) induction chemo-immunotherapy with cisplatin/docetaxel/durvalumab/tremelimumab. Machine Learning techniques were used to predict pathological complete response (pCR) after induction therapy. Results: The tested classifier methods (LDA, SVM, LR, RF, DT, and XGBoost) allowed a distinct prediction of pCR. Highest accuracy was achieved with a low number of features represented as principal components. Immune parameters obtained from the absolute difference (lT2-T1l) allowed the best prediction of pCR. In general, less than 30 parameters and at most 10 principal components were needed for highly accurate predictions. Across several datasets, cells of the innate immune system such as polymorphonuclear cells, monocytes, and plasmacytoid dendritic cells are most prominent. Conclusions: Our analyses imply that alterations of the innate immune cell distribution in the peripheral blood following induction chemo-immuno-therapy is highly predictive for pCR in HNSCC.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Chemotherapy; HNSCC; Immune phenotyping; Immunotherapy; Induction therapy

Progress Patterns under Radioimmunotherapy - clinical Evaluation of the prospective STICI Study - Schubert, Philipp; Schweizer, Claudia; Roesch, Johannes; Haderlein, Marlen; Rutzner, Sandra; Semrau, Sabine; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Hecht, Markus (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Prospective Assessment of the Inflammation Parameters in Blood Counts and Blood Serum as prognostic/predictive Parameters for Treatment with Immune Checkpoint-Inhibitors - Schweizer, Claudia; Haderlein, Marlen; Schubert, Philipp; Zhou, Jianguo; Semrau, Sabine; Rutzner, Sandra; Gostian, Antoniu-Oreste; Frey, Benjamin; Donaubauer, Anna-Jasmina; Eckstein, Markus; Becker, Ina; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Prospective development and validation of a liquid immune profile-based signature (LIPS) to predict response of patients with recurrent/metastatic cancer to immune checkpoint inhibitors - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Eckstein, Markus; Sun, Roger; Ma, Hu; Schubert, Philipp; Schweizer, Claudia; Fietkau, Rainer; Deutsch, Eric; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background The predictive power of novel biological markers for treatment response to immune checkpoint inhibitors (ICI) is still not satisfactory for the majority of patients with cancer. One should identify valid predictive markers in the peripheral blood, as this is easily available before and during treatment. The current interim analysis of patients of the ST-ICI cohort therefore focuses on the development and validation of a liquid immune profile-based signature (LIPS) to predict response of patients with metastatic cancer to ICI targeting the programmed cell death protein 1 (PD-1)/programmed cell death-ligand 1 (PD-L1) axis. Methods A total of 104 patients were prospectively enrolled. 54 immune cell subsets were prospectively analyzed in patients' peripheral blood by multicolor flow cytometry before treatment with ICI (pre-ICI; n=89), and after the first application of ICI (n=65). Pre-ICI, patients were randomly allocated to a training (n=56) and a validation cohort (n=33). Univariate Cox proportional hazards regression analysis and least absolute shrinkage and selection operator Cox model were used to create a predictive immune signature, which was also checked after the first ICI, to consider the dynamics of changes in the immune status. Results Whole blood samples were provided by 89 patients pre-ICI and by 65 patients after the first ICI. We identified a LIPS which is based on five immune cell subtypes: CD14 high monocytes, CD8+/PD-1 + T cells, plasmacytoid dendritic cells, neutrophils, and CD3 + /CD56 + /CD16 + natural killer (NK)T cells. The signature achieved a high accuracy (C-index 0.74 vs 0.71) for predicting overall survival (OS) benefit in both the training and the validation cohort. In both cohorts, the low-risk group had significantly longer OS than the high-risk group (HR 0.26, 95% CI 0.12 to 0.56, p=0.00025; HR 0.30, 95% CI 0.10 to 0.91, p=0.024, respectively). Regarding the whole cohort, LIPS also predicted progression-free survival (PFS). The identified LIPS was not affected by clinicopathological features with the exception of brain metastases. NKT cells and neutrophils of the LIPS can be used as dynamic predictive biomarkers for OS and PFS after first administration of the ICI. Conclusion Our study identified a predictive LIPS for survival of patients with cancer treated with PD-1/PD-L1 ICI, which is based on immune cell subsets in the peripheral whole blood. Trial registration number NCT03453892.
CRIS-Team Scopus Importer:2021-03-05
Keywords: biomarkers; immunotherapy; programmed cell death 1 receptor; tumor; tumor biomarkers; tumor microenvironment

Prospective Evaluation of All-lesion Versus Single-lesion Radiotherapy in Combination With PD-1/PD-L1 Immune Checkpoint Inhibitors - Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Frey, Benjamin; Schweizer, Claudia; Haderlein, Marlen; Lettmaier, Sebastian; Semrau, Sabine; Gostian, Antoniu Oreste; Zhou, Jianguo; Gaipl, Udo; Fietkau, Rainer; et al. (Frontiers in Oncology, 2020)
Background: Local ablative treatments improve survival in patients with oligometastatic disease in addition to chemotherapy. The application of immune checkpoint inhibitors prolonged patients’ survival in different tumor entities. This raises the question if patients still benefit from intensified local treatments in combination with a more efficient systemic treatment with immune checkpoint inhibitors. Methods: The prospective non-interventional ST-ICI trial investigates treatment with PD-1/PD-L1 (Programmed cell death protein 1/Programmed cell death 1 ligand 1) immune checkpoint inhibitors and radiotherapy in different tumor entities. Patients who started radiotherapy and immunotherapy concomitantly were included in this interim analysis. In this cohort patients with all-lesion radiotherapy (all tumor lesions irradiated, al-RT) were compared to patients with radiotherapy to only a single of their tumor lesions (single-lesion radiotherapy, sl-RT). Endpoints of the interim analysis were progression-free survival (PFS), overall survival (OS) and time to progression (TTP). Results: A total of 104 patients were registered between April 2017 and August 2019. Fifty patients started immune checkpoint inhibitor treatment and radiotherapy concomitantly and were included. Most frequent tumor entities were non-small cell lung cancer (62%) followed by head and neck squamous cell cancer (26%). Most frequent location of radiotherapy was lung (34%) and central nervous system (20%). Median duration of follow-up was 8.6 months beginning with first administration of the immune-checkpoint-inhibitor. Median PFS was 9.2 months (95% CI, 5.8 – 12.6) in the al-RT group and 3.0 months (95% CI, 2.5 – 3.5) in the sl-RT group (p<0.001). Median OS was 11.6 months (95% CI, 8.1 - 15.1) in the al-RT group and 4.2 months (95% CI, 3.0 - 5.4) in the sl-RT group (p=0.007). Median TTP was not reached in the al-RT group compared to 4.6 months (95% CI, 1.1–8.0) in the sl-RT group (p=0.028). Univariate Cox regression analyses computed tumor entity, histology, central nervous system metastases, immunotherapy drug and al-RT as predictors of OS (with an effect p-value of ≤ 0.1). In the multivariable analysis only tumor entity and al-RT remained prognostic factors for OS. Conclusion: Patients with PD-1/PD-L1 immune checkpoint inhibitor therapy benefit from local radiotherapy to all known lesions compared to single-lesion radiotherapy regarding PFS and OS.
CRIS-Team Scopus Importer:2020-11-20
Keywords: all-lesion; immune checkpoint inhibitors; immunotherapy; oligometastatic; radiotherapy; single-lesion

Prospective evaluation of the prognostic value of immune-related adverse events in patients with non-melanoma solid tumour treated with PD-1/PD-L1 inhibitors alone and in combination with radiotherapy - Schweizer, Claudia; Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Haderlein, Marlen; Lettmaier, Sebastian; Semrau, Sabine; Gostian, Antoniu Oreste; Frey, Benjamin; Gaipl, Udo; Zhou, Jianguo; Fietkau, Rainer; et al. (European Journal of Cancer, 2020)
Background: Prospective data about the prognostic value of immune-related adverse events (irAEs) in non-melanoma solid tumours are rare. The prognostic value of irAEs in patients treated with combined radiotherapy and immunotherapy is currently unknown. Patients and methods: The prospective non-interventional ST-ICI trial investigates treatment response of tumour patients to anti–programmed cell death-ligand 1 (PD-L1) immune checkpoint inhibitors alone and in combination with radiotherapy and possible predictive markers. Patients undergoing immunotherapy or immunoradiotherapy were surveyed for irAEs. Results: A total of 104 patients were included of whom 29 patients (28%) developed irAEs. Additional radiotherapy was performed in 50 patients (48%). Main tumour entities within the entire cohort were non–small cell lung cancer (NSCLC) (44%) and head and neck squamous cell carcinoma (42%). The rate of irAEs did not differ in patients with and without radiotherapy (p = 0.668). Patients who developed irAEs had longer overall survival (OS) (median: 22.8 months versus 9.0 months without irAEs, p = 0.001) and progression-free survival (PFS) (median: 7.8 months versus 3.2 months without irAEs, p = 0.002). In the subgroup with combined radiotherapy, patients with irAEs also had longer OS (median: 22.8 months versus 7.1 months without irAEs, p = 0.005) and PFS (median: 8.8 months versus 3.0 months without irAEs, p = 0.005). On multivariate analysis only PD-L1 on tumour cells (p = 0.049) and irAEs (p = 0.001) remained independent predictors of OS. Conclusion: The development of irAEs represents a favourable prognostic parameter in patients undergoing immunotherapy and immunoradiotherapy for solid tumours.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Immune checkpoint inhibitors; Immune-related adverse events; Non-melanoma solid tumours; Prognostic parameters; Radiotherapy

Questionnaire-based detection of immune-related adverse events in cancer patients treated with PD-1/PD-L1 immune checkpoint inhibitors - Griewing, Luisa Maria; Schweizer, Claudia; Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Frey, Benjamin; Haderlein, Marlen; Weissmann, Thomas; Semrau, Sabine; Gostian, Antoniu Oreste; Müller, Sarina Katrin; Traxdorf, Maximilian; et al. (BMC Cancer, 2021)
Background: Immune checkpoint inhibitors (ICI) have become standard treatment in different tumor entities. However, safe treatment with ICI targeting the PD-1/PD-L1 axis requires early detection of immune-related adverse events (irAE). There exist different questionnaires of drug manufacturers for the detection of irAE that have not been validated so far. Methods: The prospective non-interventional ST-ICI trial studied treatment with PD-1/PD-L1 ICI alone or combined with radiotherapy. In the current analysis, the detection rate of self-reported irAE with a patient questionnaire containing 41 different questions was compared to clinician-reported irAE. Results: Between April 2017 and August 2019, a total of 104 patients were prospectively enrolled. NSCLC (44%) and HNSCC (42%) were the most frequent tumor entities. A total of 784 questionnaires were collected. A total of 29 irAE were reported by clinicians. The most frequent irAE was hypothyroidism (9%), followed by skin reactions (5%), hepatitis (4%), diarrhea (3%), and pneumonitis (3%). Questions that became significantly more often positive at time points of clinician-reported irAE were “weight change”, “difficulty to grip things”, “bloody or mucous stool” and “insomnia”. Self-reported organ-specific questions detected at least 50% of clinician-reported irAE of gastrointestinal, lung, endocrine, and skin irAE. It was not possible to detect hepatic irAE with the questionnaire. Conclusion: Questionnaires can help to detect gastrointestinal, lung, endocrine, or skin irAE, but not hepatic irAE. Questions on “weight change” and “insomnia” may help to increase the detection rate of irAE, besides organ-specific questions. These results are a valuable contribution to the future development of a specific and practicable questionnaire for early self-reported detection of irAE during ICI therapy in cancer patients. Trial registration: ClinicalTrials.gov, NCT03453892. Registered on 05 March 2018.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Immune checkpoint inhibitors; Immune-related adverse events; Patient-reported irAE; PD-1; PD-L1; Questionnaire; Side effects; Solid tumors; Toxicity

TCCIA: a comprehensive resource for exploring CircRNA in cancer immunotherapy - Wang, Shixiang; Xiong, Yi; Zhang, Yihao; Wang, Haitao; Chen, Minjun; Li, Jianfeng; Luo, Peng; Luo, Yung Hung; Hecht, Markus; Frey, Benjamin; Gaipl, Udo; Li, Xuejun; et al. (Journal for ImmunoTherapy of Cancer, 2024)
BACKGROUND: Immunotherapies targeting immune checkpoints have gained increasing attention in cancer treatment, emphasizing the need for predictive biomarkers. Circular RNAs (circRNAs) have emerged as critical regulators of tumor immunity, particularly in the PD-1/PD-L1 pathway, and have shown potential in predicting immunotherapy efficacy. Yet, the detailed roles of circRNAs in cancer immunotherapy are not fully understood. While existing databases focus on either circRNA profiles or immunotherapy cohorts, there is currently no platform that enables the exploration of the intricate interplay between circRNAs and anti-tumor immunotherapy. A comprehensive resource combining circRNA profiles, immunotherapy responses, and clinical outcomes is essential to advance our understanding of circRNA-mediated tumor-immune interactions and to develop effective biomarkers. METHODS: To address these gaps, we constructed The Cancer CircRNA Immunome Atlas (TCCIA), the first database that combines circRNA profiles, immunotherapy response data, and clinical outcomes across multicancer types. The construction of TCCIA involved applying standardized preprocessing to the raw sequencing FASTQ files, characterizing circRNA profiles using an ensemble approach based on four established circRNA detection tools, analyzing tumor immunophenotypes, and compiling immunotherapy response data from diverse cohorts treated with immune checkpoint blockades (ICBs). RESULTS: TCCIA encompasses over 4,000 clinical samples obtained from 25 cohorts treated with ICBs along with other treatment modalities. The database provides researchers and clinicians with a cloud-based platform that enables interactive exploration of circRNA data in the context of ICB. The platform offers a range of analytical tools, including browse of identified circRNAs, visualization of circRNA abundance and correlation, association analysis between circRNAs and clinical variables, assessment of the tumor immune microenvironment, exploration of tumor molecular signatures, evaluation of treatment response or prognosis, and identification of altered circRNAs in immunotherapy-sensitive and resistant tumors. To illustrate the utility of TCCIA, we showcase two examples, including circTMTC3 and circMGA, by employing analysis of large-scale melanoma and bladder cancer cohorts, which unveil distinct impacts and clinical implications of different circRNA expression in cancer immunotherapy. CONCLUSIONS: TCCIA represents a significant advancement over existing resources, providing a comprehensive platform to investigate the role of circRNAs in immuno-oncology.
CRIS-Team Scopus Importer:2024-01-26
Keywords: biomarkers; tumor; genetic markers; immunotherapy; tumor biomarkers

The Early Landscape of Immune Cell Subsets in Metastatic NSCLC Patients Treated with Immune Checkpoint Inhibitors - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Sun, R.; Ma, H.; Fietkau, Rainer; Deutsch, E.; Gaipl, Udo; Hecht, Markus (JOURNAL OF THORACIC ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-07

The Role of ncRNAs in Solid Tumors Prognosis: From Laboratory to Clinical Utility - Zhou, Jianguo; Huang, Zhaohui; Slaby, Ondrej; Navarro, Alfons (Frontiers in Oncology, 2021)
CRIS-Team Scopus Importer:2021-03-05
Keywords: circular RNA; gene expression omnibus (GEO); long non-coding RNA; microRNA; the cancer genome atlas (TCGA)

Updated analysis of the phase II CheckRad-CD8 trial: First-line treatment of locally advanced head and neck squamous cell carcinoma with induction chemoimmunotherapy followed by radioimmunotherapy - Hecht, Markus; Eckstein, Markus; Kallies, Annett; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias; Brunner, Thomas; Tamaskovics, Bálint; Hinke, Axel; Zhou, Jianguo; et al. (35. Deutscher Krebskongress, Krebsmedizin: Schnittstellen zwischen Innovation und Versorgung, 2022)
CRIS-Team WoS Importer:2022-12-16